Effects of Commercial Inert Glass (CIG) Addition on Mechanical and Microstructural Properties of Chicken Hydroxyapatite (CHA) - Demirkol, N.; Oral, Ahmet Yavuz; Oktar, Faik Nuzhet; Kayali, E.S. (Trans Tech Publications, Ltd., 2013)
Hydroxyapatite (HA) can be obtained by both synthetic and natural methods. The synthetic hydroxyapatite is the most commonly used type of HA and it is highly reliable. However fabrication of synthetic hydroxyapatite is complex and expensive. The production of natural hydroxyapatite is easy and inexpensive. In spite of being a biocompatible and bioactive material, hydroxyapatite has a limited usage as an implant material because of its weak mechanical properties. For this reason, HA based composites are required to supply improvement of strength and toughness of the implant materials without losing biocompatibility. In this study, HA composites were synthesized by using natural chicken hydroxyapatite (CHA) reinforced with 5 and 10wt. % commercial inert glass (CIG) powders. Then their physical, mechanical, microstructural properties were characterized. Finally, the most suitable CIG containing CHA composite for orthopedical applications was determined.